2023
DOI: 10.1002/aws2.1349
|View full text |Cite
|
Sign up to set email alerts
|

Per‐ and polyfluoroalkyl substances in foam and dewatering streams at wastewater treatment plants

Abstract: The occurrence of per‐ and polyfluoroalkyl substances (PFAS) in wastewater treatment plants (WWTPs) is well recognized. While several studies have examined the occurrence of PFAS in WWTPs, studies assessing the extent to which unit processes impact PFAS phase distribution are relatively lacking. Herein, PFAS enrichment in foams generated during aeration and PFAS accumulation in solids dewatering streams were evaluated in WWTPs. Results of this screening‐level study showed that perfluorooctane sulfonate (PFOS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…While the wide range of concentrations of PFAS in biosolids has been attributed to differences in discharges of PFAS into the contributing sewersheds, it is likely that processes such as dilution, liquid–solid partitioning, and degradation also have an influence. , However, there has been little attention directed to characterizing the impact of these processes on the fate of PFAS during sludge treatment. Lakshminarasimman et al investigated the behavior of PFAS in pelletization, alkaline stabilization, anaerobic digestion, and aerobic digestion processes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the wide range of concentrations of PFAS in biosolids has been attributed to differences in discharges of PFAS into the contributing sewersheds, it is likely that processes such as dilution, liquid–solid partitioning, and degradation also have an influence. , However, there has been little attention directed to characterizing the impact of these processes on the fate of PFAS during sludge treatment. Lakshminarasimman et al investigated the behavior of PFAS in pelletization, alkaline stabilization, anaerobic digestion, and aerobic digestion processes .…”
Section: Introductionmentioning
confidence: 99%
“…However, the three sulfonate precursors (6:2 fluorotelomer sulfonate (6:2 FTS), N-ethyl perfluorooctane sulfoamido acetic acid (EtFOSAA), and N -methyl perfluorooctane sulfoamido acetic acid (MeFOSAA)) showed no significant transformation. Very recently, Schaefer et al found PFAS concentrations in solids dewatering streams to be considerably higher than the raw wastewater and their mass flow in this stream represented a significant portion of the overall PFAS mass exiting a WRRF . While the studies mentioned above have examined PFAS fate for individual units or streams within sludge-handling processes, none have comprehensively evaluated their fate through an entire train of processes.…”
Section: Introductionmentioning
confidence: 99%